IDENTIFIKASI MINERAL BATUAN PADA DAERAH MANIFESTASI MATA AIR PANAS DI KOYA KECAMATAN TONDANO SELATAN KABUPATEN MINAHASA MENGGUNAKAN SEM-EDX DAN FTIR - Ronaldo B. rey; Cosmas Poluakan (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
Indonesia's geological conditions make a real contribution to the availability of geothermal energy in Indonesia, the types of rocks that exist in the area of ​​manifestation vary in metal and mineral content. North Sulawesi Province is one of the regions that has alteration rocks which are found in many areas of manifestation of geothermal. The purpose of this study was to determine the composition of elements and types of minerals in altered rocks in the manifestation area of ​​Koya Hot Springs, South Tondano District, North Sulawesi Province. The method used is the electron beam method on SEM, and EDX uses the energy dispersive X-ray and FTIR methods. The results of the analysis on SEM-EDX showed that in sample-1 the rocks in the hot springs had elements containing 30.51% silica (Si) minerals and 69.49% oxygen (O) while in sample-2 oxygen-O 71,89 %, silica (Si) 15.28 % and aluminum (Al) 12.83%. The FTIR spectra of sample-1 with 778 cm-1 and sample-2 779 cm-1 wavenumber are quartz. This result is consistent with SEM-EDX analysis with the mineral composition is Silica (Si) and Oxygen (O).